Acceptance of e-Filing system among academicians in higher public education institution in Terengganu / Aniffarida Jusoh, Che Sakinah Ab Aziz, Nur Hafizah Aziz and Nur Izatul Asma’ Zulkepli - Jusoh, Aniffarida; Ab Aziz, Che Sakinah; Aziz, Nur Hafizah; Zulkepli, Nur Izatul Asma’ (2011)
In information research, the study on user’s acceptance of information system has always been an interest when a new system is developed and implemented. An information system is developed to improve productivity and increase efficiency in an organization. Nowadays, in Malaysia the Electronic Government offered initiatives to launch in order to lead this country into the advance improved in the technologies which to provide service for the Malaysian. Under the Electronic Government Flagship Application there is Electronic E-filing (E-filing) that has been introduced in 2006 as one of the government services for the citizen to pay their tax annually. It is also hoped that the Malaysians able to adapt the technologies for their usage in daily works. It also will improve the information flows and processes within government to improve the speed and quality of policy development, coordination and enforcement. Therefore, this research is to bring up this e-filing topic on “Acceptance Level of E-filing among Academicians in Higher Public Education Institutions in Terengganu”. To measure the acceptance levels, the TAM model has been used to determine whether the acceptance of the system has lead to the usage of the system and subsequently helps to improve the citizen or even organization efficiency. Thus, one of the objectives of this research project is to investigate the level of e-filing acceptance. Other than that, it is to identify the factors that influence the academicians to accept the e-Filing system. Two hundred and forty-eight respondents which were the academicians in Politeknik Sultan Mizan Zainal Abidin and Universiti Teknologi MARA Terengganu had been chosen to go under the survey. Those were given two weeks to complete the questionnaires. The first 88 completed questions via the first round and an additional 119 completed survey has resulting in 207 completing the questionnaires. This is 83.46% of return rate. The result revealed that the respondent or academicians’ acceptance level of E-filing system is one of the new ways in making tax payment annually based on ease of use and usefulness of the system to the users. Since the Government introduced the E-filing as a medium for the tax payers and business, the process are being accepted and continued to use in the future. In addition, the academicians were also agreed that E-fling is ease and useful in doing the tax payment.